Investigation of the presence of an aliphatic biopolymer in cyanobacteria: Implications for kerogen formation - Steve Skill (Organic Geochemistry, 2015)
Algaenan has been suggested to be one of the main precursors and contributors to kerogen deposits. Its aliphatic structure has been shown in a variety of microalgae strains. Algaenan is a non-hydrolysable and insoluble biomolecule with a very high molecular weight. There is considerable uncertainty about the formation and preservation of algaenan which led to the current kerogen formation and the implications on the global carbon cycle. We aim to prove our current hypothesis - that the cyanobacteria Chlorogloeopsis fritschii may synthesis a similar resistant biomacromolecule to algaenan. This could explain some of the discrepancies in the published literature concerning algaenan. The two microalgae Pseudochoricystis ellipsoidea and Scenedesmus obliquus as well as the cyanobacteria were subjected to harsh solvent extraction and hydrolysis steps to obtain the in-soluble and non-hydroysable macromolecule algaenan. The residues from all three strains were analysed by Pyrolysis-GC-MS and Solid-state NMR. The analysis revealed that the strain Chlorogloeopsis fritschii indeed contains algaenan or a resistant biomacromolecule very similar, exhibiting the characteristic aliphatic structure diagnostic to algaenan. Due to the robust nature of C. fritschii compared to the Eukaryotes to prevail extreme environments such as freezing, thawing, desiccation and overheating conditions which were prevalent in primeval earth, it could have significantly contributed to kerogen formation and the global carbon cycle.